IMPLEMENTASI PERATURAN GUBERNUR BALI NOMOR 26 TAHUN 2020 TENTANG SISTEM PENGAMANAN LINGKUNGAN TERPADU BERBASIS DESA ADAT TERHADAP PENGAMANAN LINGKUNGAN DI BANJAR PENAKA TAMPAKSIRING - Citrawati, Ni Nengah Agustin; Manika, Agus Surya; Widiantara , I Made Surya (Kerta Dyatmika, 2025)
Article 22 of Bali Governor Regulation Number 26 of 2020 concerning the Integrated Environmental Security System Based on Traditional Villages (Desa Adat) explicitly stipulates that pecalang (traditional security personnel) who have obtained a Gada Pratama Certificate may be seconded to assist in the implementation of limited police duties. This provision underscores that the existence and number of certified pecalang are critical factors in the effective implementation of the said regulation, particularly amid increasing urbanization and rural to urban migration. This study aims to analyze the implementation of Bali Governor Regulation Number 26 of 2020 in the Traditional Village of Tampaksiring, Banjar Penaka, Tampaksiring District, Gianyar Regency, and to identify the obstacles encountered in its enforcement. The research employs an empirical legal method with a sociological (law in action) approach, focusing on societal behavior and the practical effectiveness of legal norms. The findings indicate that the regulation has been implemented through the establishment of Bankamda, which serves as the forerunner of the Sipandu Beradat system. This system is expected to function as a preventive measure to avoid conflicts and to support the police in carrying out preventive and pre-emptive security efforts. However, the implementation faces several challenges, including a lack of understanding among Bankamda members regarding their core duties and procedures, limited budget and infrastructure, and insufficient community involvement. In conclusion, Sipandu Beradat in the Traditional Village of Tampaksiring has been effectively implemented within its delegated authority. Nevertheless, to optimize its execution, improvements are needed in member training, budget allocation, and active public participation.